Seismic Versus Sonic Revisited - Suprajitno Munadi (Testing Center for Oil and Gas LEMIGAS, 2009)
The sonic log enables all features along the depth scale can be correlated with all features in the ime scale as found in the seismic section. However, this sonic log must beThe sonic log enables all atures along the depth scale can be correlated with all features in the time scale as found in the seismic section. However, this sonic log must be corrected to the time-depth curve obtained from the check shot survey. The problem arises when some zones around the borehole such as the invaded zones or the flushed zones exhibit dispersive properties. This dispersive properties causes discrepancies between integrated sonic transit time and the time-depth curve. As a result, the synthetic seismogram generated from the sonic log will not match with the corresponding seismic section. To solve this problem, a practical method for correcting the discrepancies is presented in this paper. Although the method is inspired by paper published in the seventies, but the way to approach the problem is different. This problem looks simple, but its effect on mapping top and bottom of the reservoir is important. An example of implementation from the real field is also given. corrected to the time-depth curve obtained from the check shot survey. The problem arises when some zones around the borehole such as the invaded zones or the flushed zones exhibit dispersive properties. This dispersive properties causes discrepancies between integrated sonic transit time and the time-depth curve. As a result, the synthetic seismogram generated from the sonic log will not match with the corresponding seismic section. To solve this problem, a practical method for correcting the discrepancies is presented in this paper. Although the method is inspired by paper published in the seventies, but the way to approach the problem is different. This problem looks simple, but its effect on mapping top and bottom of the reservoir is important. An example of implementation from the real field is also given.